Appetite and its discontents science, medicine, and the urge to eat, 1750-1950 - Williams, Elizabeth Ann 1950- (The University of Chicago Press, 2020)
"Historians have begun to explore why and how eating has become problematic for more and more people. But so far little attention has been given to the problem of appetite -- the changing ways that the appetite for food is formed or how the views of scientific and medical experts on the subject have developed over time. In this book, Elizabeth Williams traces the history of academic inquiry into appetite's nature and functioning in the two centuries between 1750 and 1950, from the mid-Enlightenment to the dawn of big science. She reveals how appetite and eating came to be an object of scientific study by turning to advances in physiology, natural history, medicine, and, from the late nineteenth century, psychology and ethology. The author's goals are capacious, however, for she aims not only to convey the development of the science but, in so doing, to root out the cause of our modern nutritional disarray"--